Strategi Place dalam Pemasaran Rumah Sakit di Indonesia; Systematic Review - Bandaso, Asriyanti; Kusumowardhan, Dyani; Tanjung, Herlin Putri; Marliani, Lili; Mokoginta, Megadianty (UI Scholars Hub, 2020)
Hospitals must have a good marketing plan to increase patient interest in using its services. Marketing mix is a marketing strategy consisting of product, price, place, promotion, people, process and physical evidence. The Place Strategy refers to the ease of consumers accessing services. For this reason, we want to know how the role of place strategy in hospital marketing mix in Indonesia. This systematic review uses the PRISMA method. Searching uses Google Scholar and Garuda Ristekdikti electronic databases. Inclusion criteria, research articles, published from 2010 to 2019, and carried out in Indonesia. The keywords are